The Use of Deixis in Taylor Swift’s Cowboy Like Me - Dayana, Sri; Syatroh, Isry Laila; Naksabandi, Arip (IKIP Siliwangi, 2025)
Deixis is a pragmatic study that examines an expression that refers to the speaker's condition and can only be explained by the speaker himself. In this study, researchers examined the types of deixis and their meanings in the lyrics of singer Taylor Swift's song